Empowering Local Economy Through Identification and Development of Agricultural Assets in Barbaran Village - Kholijah, Siti (PT Agung Media Publisher, 2024)
This community service journal explores the implementation of the Asset-Based Community Development (ABCD) approach to empower the local economy of Barbaran Village through the identification and development of agricultural assets. Barbaran Village, located in [specific region], is predominantly an agricultural community with abundant natural resources but faces economic challenges, including low income levels and limited market access. The ABCD methodology was employed to address these challenges by focusing on mobilizing local assets and capacities. The study followed a structured process: engaging the community to build trust and collaboration, mapping existing agricultural assets such as fertile land, traditional farming knowledge, and local crops, and developing strategies to utilize and enhance these assets for economic growth. Key initiatives included training programs to improve agricultural practices, forming cooperatives to enhance market access, and introducing sustainable farming techniques to boost productivity and environmental sustainability. The findings indicate that the ABCD approach effectively empowered the local economy. Community involvement fostered a sense of ownership and commitment, while improved agricultural practices and cooperative formation increased farmers’ skills and income levels. Sustainable farming methods not only enhanced crop yields but also preserved soil health. The ABCD methodology significantly contributed to the economic empowerment of Barbaran Village by leveraging existing agricultural assets. This approach can serve as a model for other rural communities facing similar challenges. Future efforts should focus on scaling successful initiatives and fostering broader collaborations to sustain economic growth. The study underscores the potential of asset-based strategies in driving sustainable development and improving local economies.